ENVIRONMENTAL FOOTPRINTS CAUSED BY THE OPERATION OF OPEN-PIT MINES AND THE POSSIBILITY OF MULTIFUNCTIONAL USE OF THE OCCUPIED SPACE - Ivo Galić; Josip Kronja; Ivica Pavičić; Ivan Soldo (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta, 2024)
Open-pit mines of mineral raw materials play a key role in the development of society and economy. However, their construction and operation often have a significant environmental footprint, which includes physical, chemical and biological changes in the natural environment. This paper investigates the environmental impacts of open-pit mining and emphasizes the importance of integral use of the affected area in order to minimize negative impacts and at the same time promote their beneficial functions. The paper presents examples of rehabilitation and repurposing of open-pit mines and the possible multifunctional use of space.